Misconduct in The Judicial Process: Advocates as Bribery Offenders - Rambe, Epi Santri Dewi; Mintarsih, Mimin (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2024)
Advocates are one of the law enforcement tools. Meanwhile, in some cases, advocates still commit bribery crimes while carrying out their duties. This study aims to analyze the practice of irregularities in the judicial process carried out by Advocates and analyze the application of sanctions for Advocates who are perpetrators of bribery crimes. The research method used is normative juridical with a regulation-legislation approach and a case approach. The results show that irregularities in the judicial process often occur with advocates involved in bribery crimes, thereby damaging the integrity of the legal system and reducing public trust in law enforcement. In Indonesia's positive law, several criminal provisions can be applied to advocates who commit bribery crimes, namely the Criminal Code (Article 209, Article 418, Article 419, Article 420 (1) and (2)), the TPS Law (Article 3), the PTPK Law (Article 5 (1), Article 6 (1), Article 6 (1) letter b, Article 12 letter d, Article 13). In addition, for Advocates who commit bribery crimes, sanctions can be applied based on the Indonesian Code of Ethics for Advocates as the highest law for the profession in carrying out their duties. As a noble and honorable profession, advocates who are perpetrators of bribery crimes have harmed the dignity and honor of their profession. It can be concluded that the implementation of sanctions for advocates involved in bribery crimes in Indonesia is divided into two types: the application of sanctions based on Indonesia's criminal law and the Indonesian Code of Ethics for Advocates. Both regulate the legal consequences for these crimes from different perspectives but aim to solve irregularities in the judicial process.